Deep model of lithosphere of central part of the Antarctic peninsula from DSS data and high pressures petrophysics - V. A. Korchin; P. A. Burtny; E. E. Karnaukhova; S. S. Chulkov (Ukrainian Antarctic Journal, 2010)
Models of mineral matter distributing with a depth along seismic DSS 10, 12, 13 profiles near the station «Academik Vernadsky» are built.